Participatory diagnosis and adaptive management of small-scale fisheries in the Niger River Basin - Béné, Christophe; Kodio, A.; Lemoalle, J.; Mills, D.; Morand, P.; Ovie, S.; Sinaba, F.; Tafida, A. (CGIAR Challenge Program on Water and Food, 2009)
In a broad sense, analysis of ‘resilience’ is about the capacity of systems to adapt to shocks, recognizing that disturbance and change are integral component of complex systems. More formally, resilience analysis proposes to focus on mechanisms and processes that help systems absorbing perturbations and shocks, and coping with uncertainty and risks. Defined in such a way, the concept of resilience thus appears particularly useful for the management of small-scale fisheries. However, while the resilience concept is appealing, particularly in the face of the failure of current management approaches, the danger is that it remains largely academic and theoretical, and not of a great help in effectively improving the way natural resources are managed on the ground. The challenge, therefore, lies in a pragmatic approach to operationalizing the concept of resilience and making its implementation on the ground practical and meaningful. In this project we propose a framework aimed at this objective and we test it in the specific context of small-scale fisheries in the Niger River Basin.